Effect of Mg–Ga alloy intermetallic compounds on the properties of soluble aluminum alloy. (May 2022) - Hui, Weihua; Sun, Liang; Zhou, Yong; Gao, Yimin; Zhai, Wenyan; Dong, Hui; Liu, Yanming; Gao, Qian; Peng, Jianhong
Abstract: Numerous soluble aluminum alloys are the overriding applications in hydraulic fracturing technology applied in oil and gas field exploitation or biomaterial utilization. The solubility of aluminum alloy attributes to that of superficial hard and dense alumina film damage or broken, in such cases several representative low melting point metals addition will play a part, such as Ga, In, Sn, etc. Typically, aluminum alloys tends to be brittle due to Ga addition, while Mg element can be supposed to enhance its strength according to four representative Mg–Ga alloy intermetallic compounds, which is Mg2 Ga, MgGa, Mg5 Ga2 and MgGa2, respectively. In present article, the first-principles calculation method was introduced to theoretically investigate the mechanical properties of the four Mg–Ga phases. The thermodynamic properties, structural stability, electronic structure, elastic properties and performance under pressure of four Mg–Ga intermetallic compounds were also investigated. Obviously, from the perspective of electronic structure, Mg is the electronic provider and Ga is the electronic acceptor in these compounds. According to the ionization degree calculation, the interaction between Mg and Ga ions in Mg5 Ga2 phase is the strongest. In MgGa phase, the s -state electron energy density of Ga atom is the highest, so the s -state electron of Ga atom contributes the most to the contact potential between the grain boundary phase and the Al matrix. Therefore, the driving force of MgGa anodic dissolution has a decisive advantage which is reflected that its corrosion rate and the hydrogen production rate is the maximum. Thus the analysis of four intermetallic compounds mechanical properties, the bulk modulus B of four Mg–Ga intermetallic compounds is basically similar, indicating that they have similar compressive deformation resistance and fracture resistance. At 0 GPa, the young's modulus E and shear modulus G of Mg5 Ga2 is the highest. The results show that Mg5 Ga2 has the largest stiffness and plastic deformation resistance. Highlights: The effects of MgGa, Mg2 Ga, Mg5 Ga2 and MgGa2 in soluble aluminum alloy were analyzed by first-principles calculation method. MgGa will lead to a faster corrosion rate and the fastest hydrogen production rate in soluble aluminum alloys. Mg5 Ga2 behave the excellent stiffness and resistance to plastic deformation which enhances strength of the aluminum alloy.